WC – (Cu: AISI304) composites processed from high energy ball milled powders. (November 2019) - Cardoso, J.P.; Puga, J.; Rocha, A.M. Ferro; Fernandes, C.M.; Senos, A.M.R.
Abstract: Alternative binders to cobalt, based on stainless steel (SS, AISI304) and copper were investigated for tungsten carbide (WC) based cemented carbides. The binder content was fixed at 12 wt%, and the Cu:SS ratio varied in proportions of 0:1, 1:5, 1:2, 1:1, 1:0. High energy ball milling was applied to ensure high homogenization, nanometric particle size and mechanical alloying of binder elements in the powders' mixtures. To assess an adequate sintering route, wettability testing and constant heating rate dilatometry in vacuum were performed. The composites were analyzed in terms of their structural, microstructural and mechanical characteristics. The poor wettability of melted Cu on WC surfaces was increased by alloying it with SS and highly dense compacts could be successfully attained at reduced vacuum sintering temperatures with binders having a Cu:SS ratio equal to or lower than 1:2. The microstructures show secondary phases and significant grain coarsening during sintering, whereas the average grain size was kept in the nanometric range. The composites that attained almost full densification present high hardness, comparable to that of nanometric WC-12Co cemented carbides processed by similar routes, but lower toughness values. Graphical abstract: Unlabelled Image Highlights: Alloying Cu with stainless steel by HEBM increases the wettability of Cu on WC. WC - (Cu, Fe, Cr, Ni) nanopowders can be successfully densified at reduced temperatures. WC - (Cu, Fe, Cr, Ni) nanocomposites present high hardness and moderate toughness.